Spatial-temporal redistribution of point defects in three-layer stressed nanoheterosystems within the limits of self-assembled deformation-diffusion model - Peleshchak, R.M.; Kulyk, N.Ya.; Doroshenko, M.V. (Condensed Matter Physics, 2015)
The model of spatial-temporal distribution of point defects in a three-layer stressed nanoheterosystem GaAs/InxGa₁-xAs/GaAs considering the self-assembled deformation-diffusion interaction is constructed.